Preparation method and application of molecular sieve type adsorbent
Through the preparation method of molecular sieve type adsorbent, the pollution and high cost problems caused by alkaline earth metal load in traditional methods are solved, and efficient and environmentally friendly adsorbent preparation is achieved, which improves adsorption capacity and selectivity and reduces production costs.
Patent Information
- Application Number
- CN202210904580.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-29
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2042-07-29
AI Technical Summary
The existing molecular sieve adsorbents have problems of contamination and high cost during alkaline earth metal loading, especially due to the low discharge and adsorption capacity of barium-containing wastewater caused by traditional liquid ion exchange methods.
A method of preparing molecular sieve type adsorbent is adopted. The solution volume does not exceed the saturated water absorption of the product through the molding of molecular sieve, binder and pore-forming agent, in-situ crystallization treatment, target ion removal treatment and target ion loading. , spraying small droplets and high temperature treatment to evenly distribute load substances, reduce wastewater discharge and improve load efficiency.
It realizes environmentally friendly and low-cost adsorbent preparation, improves adsorption capacity and selectivity, reduces production costs, and has uniform distribution of load substances and excellent adsorption performance.
Smart Images

Figure CN115970638B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adsorbents, and in particular relates to a preparation method and application of a molecular sieve type adsorbent. Background Art
[0002] Adsorbents are widely used in various fields of chemical production. Products such as p-xylene, p-cresol, and oxygen can be prepared through adsorption separation. Taking the production of polyester as an example, p-xylene (PX) is an important basic chemical raw material. It is mainly used to produce purified terephthalic acid, and then to produce polyester. Polyester is widely used in the production of polyester fibers, various packaging materials, and industrial components. At present, the main p-xylene production route is to use naphtha as raw material, and obtain mixed C8 aromatics containing p-xylene, o-xylene, m-xylene, and ethylbenzene through catalytic reforming, aromatic extraction, disproportionation, isomerization and other processing processes. Since C8 aromatic isomers have similar boiling points, it is difficult to separate high-purity products by distillation technology. The simulated moving bed adsorption separation process is generally used in industry to achieve the separation and purification of p-xylene. The core is the development and application of high-efficiency adsorbents. At present, the industry generally uses FAU zeolite adsorbents exchanged by barium and potassium ions alone or in combination.
[0003] Molecular sieve is a type of aluminosilicate crystal material with a regular pore structure. There are many holes of specific sizes in the molecular sieve crystal, and the holes are connected by holes (also called "windows"). Since the molecular sieve can adsorb molecules smaller than its pore size into the holes and exclude molecules with larger sizes from its holes, it plays the role of screening molecules, hence the name molecular sieve.
[0004] This type of material is widely used as a catalyst or adsorbent in the fields of petroleum processing and fine chemicals. However, molecular sieves are generally in powder form and cannot be directly used in fixed bed adsorption devices. Therefore, they need to be molded with a binder to provide a certain mechanical strength during use. The presence of the binder reduces the content of effective active components in the molded adsorbent. Generally, the binder is zeolized by alkaline solution treatment to overcome the problem of reduced adsorption capacity of the adsorbent caused by the binder.
[0005] In addition, it is necessary to exchange a certain type and amount of cations to adjust the electrochemical properties of the molecular sieve so that it can selectively adsorb specific types of substances. For example, Na-type X molecular sieves do not have adsorption selectivity for C8 aromatics. Generally, soluble barium salts or potassium salts are used to exchange ions on NaX beads to adjust their electrochemical properties and thus improve the adsorption selectivity of xylene. Take the barium ion exchange of NaX beads as an example:
[0006] One of the methods is a solid-state ion exchange method disclosed in the patent document (application number: CN00123514.1), which first mixes molecular sieves, barium salts and binders and grinds them into particles with a particle size of less than 300 μm, then rolls them into particles, bakes them at 500-580°C, and then uses deionized water to wash away the exchanged sodium ions, thereby obtaining a paraxylene adsorbent. This method reduces the discharge of barium-containing wastewater, but the addition of barium salts during molding makes it impossible to perform crystal transformation on the binder, and the adsorption capacity of the adsorbent is low.
[0007] Another method is to first mix the molecular sieve and the binder, etc., and then roll-form and calcine at high temperature, and then perform in-situ crystallization in an alkaline system to achieve crystallization treatment of the binder, and finally use an aqueous solution of barium salt to perform cation exchange on the NaX beads. During the liquid ion exchange process, the NaX molecular sieve and the aqueous solution of the barium salt come into contact, and the barium ions in the solution enter the molecular sieve under the concentration gradient and heat drive, while the sodium ions on the molecular sieve are exchanged and enter the solution. In order to maintain the concentration gradient between the solution and the molecular sieve, the barium ions in the solution are greatly excessive, so barium-containing wastewater is inevitably produced. As a highly toxic substance, the discharge of soluble barium salts is strictly restricted, and the treatment of barium-containing wastewater will increase production costs.
[0008] Based on this, it is meaningful to find an environmentally friendly, low-cost preparation method that can guarantee the performance of the adsorbent. Summary of the invention
[0009] 1. Problem to be solved
[0010] In view of the existing technology of molecular sieves such as Ba 2+ , Sr 2+ The pollution problem when alkaline earth metals are loaded is solved. The purpose of the present invention is to provide a method for preparing an environmentally friendly molecular sieve type adsorbent. The prepared adsorbent has excellent adsorption capacity.
[0011] 2. Technical solution
[0012] In order to solve the above problems, the technical solution adopted by the present invention is as follows:
[0013] A method for preparing a molecular sieve type adsorbent, wherein the molecular sieve type adsorbent is loaded with a component M;
[0014] At least the following steps are included:
[0015] S1. Make the molecular sieve, binder and pore-forming agent fully contact and mix, and then shape them in a certain way;
[0016] S2. high temperature treatment to obtain product A;
[0017] S3. subjecting product A to in-situ crystallization treatment in an alkaline system to obtain product B;
[0018] S4. The product B is subjected to a treatment to remove target ions to obtain a product C; wherein the target ions include ions derived from the alkaline system in S3;
[0019] S5. The solution containing M is contacted and mixed with the product C to achieve the loading of M on the product C to obtain an adsorbent;
[0020] Wherein, the saturated water absorption capacity of the product C is determined, and the amount of the solution containing M does not exceed the saturated water absorption capacity of the product C.
[0021] It should be noted here that:
[0022] Ⅰ) In S1, there is no particular requirement for the contact order of the molecular sieve, the binder, and the pore-forming agent. As a preferred embodiment, the molecular sieve and the binder are usually first mixed to form a mixture, and then the pore-forming agent is contacted and mixed with the mixture in the form of an aqueous solution, with the purpose of finally forming a "molded" product comprising the molecular sieve, the binder, and the pore-forming agent. Examples of the "molded" product include particles, strips, sheets, etc., and particles are preferred;
[0023] The "particle" molding method described herein can be a known molding method, such as a known oil column molding method, an extrusion molding method, a spray molding method, a rolling molding method, etc. There is no particular limitation on the size of the particles, which can be determined according to demand. As a preferred solution, the particles have a particle size in the range of 0.3 to 3 mm, and more preferably have a particle size in the range of 0.3 to 1 mm;
[0024] In S2, as a preferred solution, before the high temperature treatment, a drying treatment may be selectively performed at room temperature or at a temperature not higher than 200°C;
[0025] In S3, the in-situ crystallization treatment is generally carried out in an alkaline solution. As a preferred solution, the in-situ crystallization temperature is 90 to 120° C. and the crystallization time is 4 to 12 hours;
[0026] The alkaline solution generally has a concentration of 1 to 3 mol / L, and the alkali type is generally sodium hydroxide or potassium hydroxide. + , K + etc. metal cations.
[0027] II) As described herein, different types of molecular sieves may be selected for different specific applications of the adsorbent, such as depending on the target substance adsorbed by the adsorbent:
[0028] If the target substance is p-xylene or p-cresol, then alkaline earth metal-loaded FAU type molecular sieves are preferred. Further, the "FAU type molecular sieves" include X molecular sieves and Y molecular sieves. For example, "Synthesis and Characterization of FAU Zeolite Molecular Sieve and Its Membrane" (Lu Ying, Jilin University, 2014) has a detailed description of FAU type molecular sieves.
[0029] The target substance is CO. When applied to remove CO impurities in H2, "Cu-Y molecular sieve" is preferred;
[0030] The target substance is iodine. When applied to adsorb gaseous iodine, "Ag-MOR molecular sieve" is preferred.
[0031] III) In the preparation method of loading component M by the traditional liquid ion exchange method, in order to maintain the concentration gradient between the solution and the molecular sieve, the M in the solution should be excessive, so a large amount of wastewater containing M will inevitably be produced, increasing the production cost. Different from the traditional preparation method of loading component M by the cation exchange method, the preparation method of the molecular sieve type adsorbent described herein, the amount of the solution containing M does not exceed the saturated water absorption of the product C, thereby greatly reducing the amount of solution containing M and the amount of M used, greatly improving the effective utilization rate of M, avoiding the discharge of wastewater, and reducing the production cost. At the same time, this method also greatly shortens the time required for loading M, facilitates the precise control of the loading amount of M, and the resulting adsorbent still has good selection and adsorption performance.
[0032] Further, in S1, the amount of molecular sieve added is higher than the amount of binder added, but the amount of binder added accounts for no less than 5wt% of the total amount of molecular sieve and binder added; as a preferred embodiment, the amount of molecular sieve added is at least four times the amount of binder added, and the amount of binder added is no less than 5wt% of the amount of molecular sieve added; as a further preferred embodiment, the mass ratio of molecular sieve to binder added is (80-95): (5-20);
[0033] The amount of the pore-forming agent added is 1 to 5 wt% of the total weight of the molecular sieve and the binder on a dry basis; more preferably 1 to 3 wt%;
[0034] The binder is any one of kaolin, bentonite, perlite and halloysite;
[0035] The pore-forming agent is one or more of starch, lignin, polyethylene glycol and sodium carbonate.
[0036] Furthermore, in said S2, the temperature of the high temperature treatment is 550-950°C; more preferably, the temperature is 550-750°C;
[0037] The treatment time of high temperature treatment is 1 to 8 hours;
[0038] Furthermore, in S5, the solution containing M is brought into contact with the product C in the form of small droplets, then left to stand for treatment, and finally subjected to high-temperature treatment in an atmosphere containing water vapor.
[0039] It should be noted here that the M-containing solution is diffused into the pores of the molecular sieve by utilizing the gravity of the liquid, the surface tension and the adsorption of the carrier, and then the water is evaporated by drying so that M is evenly distributed on the inner surface of the molecular sieve. This not only reduces the amount of the M-containing solution used, but also improves the utilization rate of the M-containing solution, and the load distribution of M is even.
[0040] As a preferred embodiment, during the process of contacting the product C with the solution containing M in the form of small droplets, the product C is tumbled and sprayed with the solution containing M until the small balls are completely wetted.
[0041] Furthermore, in S5, the static treatment time is 30 to 120 minutes.
[0042] It should be noted that: 1) an atomizer is used to atomize the M-containing solution into tiny droplets as fine as possible. The smaller the droplets, the more conducive it is to evenly spray the solution. In order to ensure a good effect, it is hoped that the volume median diameter of the small droplets is no more than 500 μm.
[0043] II) The purpose of the "standing treatment" as described herein is to allow the solution containing M to fully diffuse into the pores of the molecular sieve, and the standing time will affect the dispersion of M on the adsorbent. If the "standing treatment time" is too short, less than 30 minutes, such as 15 minutes, the M distribution will be uneven;
[0044] III) In addition, due to the high loading amount of M in the adsorbent, the preparation method of loading component M by the traditional liquid ion exchange method usually requires a cation exchange treatment time of M of not less than 10 hours, generally 10 to 20 hours;
[0045] In the method for preparing the molecular sieve type adsorbent as described herein, the loading process of M does not exceed 2 hours.
[0046] Further, in said S5, the volume content of water vapor in the gas atmosphere during the high temperature treatment is 20-40%, and the temperature of the high temperature treatment is 350-500°C;
[0047] The high temperature treatment time is 1 to 5 hours.
[0048] It should be noted that: 1) The purpose of "high temperature treatment" as described herein is to further disperse M and reach the negative charge of the molecular sieve framework. The silicon-aluminum molecular sieve has a framework electronegativity due to the substitution of aluminum for silicon, and cations are required to balance the framework charge. The target metal ion needs to be loaded on the exchange site (i.e., the negative charge of the framework) of the molecular sieve to have adsorption activity. If the metal is unevenly dispersed and the local metal ion content is more than the number of exchange sites, metal oxides will be formed after roasting, and the metal oxides do not have adsorption activity. As the solution containing M is completely absorbed by the molecular sieve, M does not selectively enter the molecular sieve pores. During the roasting process, M is further dispersed and reaches the negative charge of the molecular sieve framework under heat drive.
[0049] II) During the high temperature treatment as described above, the purpose of introducing water vapor is to promote the migration of M in the pores of the molecular sieve, which helps to improve the uniformity of M dispersion.
[0050] Furthermore, in S4, the solution containing ammonium ions is brought into contact with the product B, and the content of the target ions in the contacted solution is detected. If the content of the target ions is ≤0.1 wt %, the removal of the target ions is completed.
[0051] Further, an ammonium salt is used to prepare a solution containing ammonium ions, wherein the concentration of the ammonium salt added is 0.05 to 0.3 mol / L;
[0052] It should be noted that the ammonium salt is soluble and is generally any one or more of ammonium chloride, ammonium carbonate and ammonium sulfate. As a preferred embodiment, during the target ion removal treatment, the treatment temperature is maintained at 60-80°C, and after the treatment is completed, the product is washed with deionized water until the pH is neutral, and then dried at a temperature not exceeding 100°C to obtain product C.
[0053] Further, the product B is placed in a container, and a solution containing ammonium ions is continuously introduced into the container;
[0054] Wherein, the container has a liquid inlet and a liquid outlet.
[0055] The volume space velocity of the solution containing ammonium ions is 2 to 8 h -1 ; The further preferred concentration is 3 to 6h -1 .
[0056] It should be noted that the basic requirement of the container is to have a liquid inlet and a liquid outlet, and there is no special requirement. As a preferred solution, the product after in-situ crystallization is generally filled in a tubular container, and an ammonium salt solution is continuously introduced until the content of the target ion in the outlet solution is less than 0.1wt%.
[0057] Furthermore, the component M is an alkaline earth metal cation. It can be a single type of metal cation or a combination of several types of metal cations; examples of such cations include Ba 2+ , Sr 2+ Based on this, component M can be Ba 2+ Component M can be Sr 2+ Component M can also be Ba 2+ and Sr 2+ .
[0058] Based on this, the molecular sieve adsorbent prepared by any of the above methods is loaded with Ba 2+ Molecular sieve adsorbent, loaded with Sr 2+ Molecular sieve adsorbent, loaded with Ba 2+ and Sr 2+ Molecular sieve adsorbent.
[0059] Based on this, the above molecular sieve type adsorbent can be fully applied to obtain target substances from the mixture by adsorption separation; such target substances can be listed as p-xylene, p-cresol, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] Figure 1 2 are the XRD patterns of Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0061] The present disclosure may be more easily understood by reference to the following description in conjunction with the accompanying drawings and examples, all of which constitute a part of the present disclosure. It should be understood that the present disclosure is not limited to the specific products, methods, conditions or parameters described and / or shown herein. Further, the terms used herein are only used for the purpose of describing specific embodiments by way of example and are not intended to be limiting unless otherwise stated.
[0062] It should also be understood that, for the sake of clarity, certain features of the present disclosure may be described herein in the context of separate embodiments, but may also be provided in combination with each other in a single embodiment. That is, unless clearly incompatible or specifically not included, each separate embodiment is considered to be combinable with any other embodiment, and the combination is considered to represent another different embodiment. Conversely, for the sake of simplicity, the various features of the present disclosure described in the context of a single embodiment may also be provided individually or in any sub-combination. Finally, although a particular embodiment may be described as part of a series of steps or part of a more general structure, each step or substructure itself may also be considered to be an independent embodiment.
[0063] Unless otherwise indicated, it should be understood that each individual element in a list and each combination of individual elements in the list will be interpreted as a different embodiment. For example, a list of embodiments represented as "A, B, or C" should be interpreted to include embodiments "A", "B", "C", "A or B", "A or C", "B or C", or "A, B, or C".
[0064] In the present disclosure, the singular forms of the articles "a," "an," and "the" also include the corresponding plural references, and a reference to a specific value includes at least that specific value unless the context clearly indicates otherwise. Thus, for example, a reference to "a substance" is a reference to at least one of that substance and equivalents thereof.
[0065] The terms including ordinal numbers such as "first" and "second" can be used to explain various components or fluids, but these components and fluids are not limited by these terms. Therefore, without departing from the teachings of the present disclosure, these terms are only used to distinguish the component / fluid from another component / fluid.
[0066] When items are described by using the conjunction terms "... and / or...," etc., the description should be understood to include any one of the associated listed items and all combinations of one or more thereof.
[0067] In general, the use of the term "about" indicates an approximate value that may vary depending on the desired properties obtained by the disclosed subject matter, and will be interpreted in a context-dependent manner based on function. Therefore, one of ordinary skill in the art will be able to interpret a certain degree of difference on a case-by-case basis. In some cases, the number of significant figures used when expressing a particular value can be a representative technique for determining the difference allowed by the term "about". In other cases, a gradient in a range of values can be used to determine the range of differences allowed by the term "about". Further, all ranges in this disclosure are inclusive and combinable, and reference to the values stated in the range includes each value within the range.
[0068] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs; the terms used herein and / or include any and all combinations of one or more of the associated listed items.
[0069] The present invention is further described below in conjunction with specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. The essential characteristics and remarkable effects of the present invention can be reflected from the following examples, and the described embodiments are part of the embodiments of the present invention, rather than all the embodiments, and therefore, they do not limit the present invention in any way, and those skilled in the art make some non-essential improvements and adjustments based on the content of the present invention, which all belong to the protection scope of the present invention.
[0070] In the following specific embodiments:
[0071] The detection instruments used are: online mass spectrometer (model Hiden HPR20), gas chromatograph (model Agilent7890B), inductively coupled plasma emission spectrometer (model ThermoiCAP 7000).
[0072] The method for performing the in-situ crystallization treatment is as follows: placing the product A in a mixed solution of 1.6 mol / L NaOH and 0.4 mol / L KOH, and performing a crystallization treatment at 100° C. for 6 hours.
[0073] The barium exchange degree of the adsorbent is calculated as follows: the molar amount of barium in the sample is W1, the molar amount of aluminum is W2, and the barium exchange degree is [(2*W1) / W2]*100%. In the following examples, the barium content in the sprayed barium solution is theoretically NH4 + The barium exchange degree of the type molecular sieve reaches 99%.
[0074] The specific method for determining the saturated water absorption rate of the sample is: add 1gNH4 + Add water drop by drop into the molecular sieve powder sample while stirring continuously until the sample surface is completely wetted, and the saturated water absorption per unit mass of the sample is obtained. By zeolizing the binder, the active component content in the adsorbent reaches more than 98%, so it can be considered that NH4 + The saturated water absorption of the powder and the pellets is the same.
[0075] The specific method for determining the adsorption capacity of the adsorbent is: load a certain mass of adsorbent into a fixed bed reactor, purge in nitrogen at 550°C for 1 hour, cool to 40°C, introduce 500 ppm toluene (nitrogen balance) until adsorption is saturated, and use an online gas mass spectrometer to quantitatively analyze the gas composition at the tail end of the adsorbent. The adsorption capacity of the adsorbent is the amount of toluene adsorbed before the breakthrough point.
[0076] The specific method for determining the adsorption selectivity of the adsorbent is as follows: 100 ml of the adsorbent is loaded into the fixed bed reactor and tapped to fill it. After the adsorbent is dehydrated and activated, p-diethylbenzene desorbent is introduced to evacuate the gas in the system, the temperature is raised to 175°C, and the pressure is raised to 0.8 MPa;
[0077] 12 ml of C8 aromatic hydrocarbon mixture was introduced: 16.2 wt% of ethylbenzene (EB), 17.4 wt% of p-xylene (PX), 40.8 wt% of m-xylene (MX), and 25.6 wt% of o-xylene (OX);
[0078] Then, a desorbent is introduced to desorb the C8 aromatics, and the desorbed liquid is collected at the reactor outlet and its composition is analyzed by gas chromatography. The C8 aromatics are separated due to different desorption speeds, and the adsorption selectivity is used to measure the degree of separation.
[0079] Example 1
[0080] The ratio of NaX molecular sieve (a typical FAU type molecular sieve) to kaolin is 90:10;
[0081] 1. Stir NaX molecular sieve and kaolin evenly, add appropriate amount of polyethylene glycol aqueous solution to form small balls while rolling and forming; the amount of polyethylene glycol added is 1wt% of the total dry weight of the molecular sieve and kaolin; the amount of the polyethylene glycol aqueous solution is 20wt% of the total dry weight of the molecular sieve and kaolin; the particle size of the small balls is 0.3-1mm.
[0082] 2. The pellets were dried at 100°C and then calcined at 800°C for 2 hours to obtain an adsorbent precursor (i.e., product A, hereinafter referred to as product A). The adsorbent precursor was crystallized in an alkaline solution to obtain crystallized pellets (i.e., product B, hereinafter referred to as product B).
[0083] 3. The crystallized pellets were placed in a stainless steel tube container and 0.3 mol / L ammonium chloride solution was introduced until the sodium content in the outlet solution was less than 0.1 wt%. The exchange temperature was 60°C and the volume space velocity was 2 h -1 After the exchange, the product was washed with deionized water until the pH was neutral and dried at 100°C to obtain NH4X pellets (i.e., product C, hereinafter referred to as product C).
[0084] 4. Spray the NH4X pellets with 0.1 mol / L barium chloride solution while turning them over until the pellets are completely wetted (so that the solution contacts the pellets in the form of spray droplets), let stand for 30 minutes, and calcine at 500°C for 1 hour after drying.
[0085] The prepared adsorbent (hereinafter referred to as BaX molecular sieve) has a barium exchange degree of 98.6%. The adsorption capacity and selectivity test results are shown in Table 1.
[0086] Example 2
[0087] The ratio of NaX molecular sieve and bentonite is 86:14;
[0088] NaX molecular sieve and bentonite are mixed in a certain proportion, and then starch accounting for 2 wt% of the total dry weight of the molecular sieve and bentonite is added, and the mixture is fully stirred and rolled to obtain small balls with a particle size of 0.3-1 mm.
[0089] The pellets were dried at 200° C. and then calcined at 700° C. for 4 hours to obtain an adsorbent precursor. The adsorbent precursor was crystallized in an alkali solution to obtain crystallized pellets.
[0090] The crystallized pellets were placed in a stainless steel tube container and 0.05 mol / L ammonium sulfate solution was introduced until the sodium content in the outlet solution was less than 0.1 wt%. The exchange temperature was 80°C and the volume space velocity was 8 h -1 After the exchange, the NH4X pellets were washed with deionized water until the pH was neutral and dried at 100°C.
[0091] The NH4X pellets were sprayed with 0.1 mol / L barium nitrate solution while turning them over until the pellets were completely wetted (so that the solution came into contact with the pellets in the form of spray droplets), left to stand for 60 minutes, and then dried and calcined at 50°C for 5 hours.
[0092] The barium exchange degree of the prepared BaX molecular sieve is 99.1%. The adsorption capacity and selectivity test results are shown in Table 1.
[0093] Example 3
[0094] The ratio of NaX molecular sieve to halloysite is 92:8;
[0095] The NaX molecular sieve and halloysite are mixed, and then lignin accounting for 3 wt% of the total dry weight of the molecular sieve and the halloysite is added, and the mixture is fully stirred and rolled to form small balls with a particle size of 0.3 to 1 mm.
[0096] The pellets were dried at 120° C. and then calcined at 725° C. for 3 hours to obtain an adsorbent precursor. The adsorbent precursor was crystallized in an alkaline solution to obtain crystallized pellets.
[0097] The crystallized pellets were placed in a stainless steel tube container and 0.1 mol / L ammonium carbonate solution was introduced until the sodium content in the outlet solution was less than 0.1 wt%. The exchange temperature was 80°C and the volume space velocity was 6 h -1 . Wash and dry to obtain NH4X pellets.
[0098] The NH4X pellets were sprayed with 0.06 mol / L barium chloride solution while turning them over until the pellets were completely wetted (so that the solution came into contact with the pellets in the form of spray droplets), left to stand for 120 minutes, and then dried and calcined at 400°C for 4 hours.
[0099] The prepared BaX molecular sieve has a barium exchange degree of 99.0%. The adsorption capacity and selectivity test results are shown in Table 1.
[0100] Example 4
[0101] The ratio of NaX molecular sieve to kaolin is 88:12;
[0102] The NaX molecular sieve and kaolin are mixed evenly in a certain proportion, and a proper amount of sodium carbonate aqueous solution is added to form small balls while rolling and forming; the amount of sodium carbonate added is 5wt% of the total dry weight of the molecular sieve and kaolin. The amount of the sodium carbonate aqueous solution is 20wt% of the total dry weight of the molecular sieve and kaolin; the particle size of the small balls is 0.3-1mm.
[0103] The pellets were dried at 140° C. and then calcined at 650° C. for 5 hours to obtain an adsorbent precursor. The adsorbent precursor was crystallized in an alkali solution to obtain crystallized pellets.
[0104] The crystallized pellets were placed in a stainless steel tube container and 0.25 mol / L ammonium chloride solution was introduced until the sodium content in the outlet solution was less than 0.1 wt%. The exchange temperature was 70°C and the volume space velocity was 3 h -1 . Wash and dry to obtain NH4X pellets.
[0105] The NH4X pellets were sprayed with 0.08 mol / L barium acetate solution while turning them over until the pellets were completely wetted (so that the solution came into contact with the pellets in the form of spray droplets), and then allowed to stand for 100 minutes. After drying, they were calcined at 50°C for 3 hours.
[0106] The barium exchange degree of the prepared BaX molecular sieve is 98.5%. The adsorption capacity and selectivity test results are shown in Table 1.
[0107] Example 5
[0108] The ratio of NaX molecular sieve to kaolin is 82:18;
[0109] The NaX molecular sieve and kaolin are mixed, and then 3 wt % of starch accounting for the total dry weight of the molecular sieve and kaolin is added, and the mixture is fully stirred and rolled to obtain small balls with a particle size of 0.3-1 mm.
[0110] The pellets were dried at 160° C. and then calcined at 600° C. for 6 hours to obtain an adsorbent precursor. The adsorbent precursor was crystallized in an alkali solution to obtain crystallized pellets.
[0111] The crystallized pellets were placed in a stainless steel tube container and 0.15 mol / L ammonium carbonate solution was introduced until the sodium content in the outlet solution was less than 0.1 wt%. The exchange temperature was 65 °C and the volume space velocity was 3 h -1 . Wash and dry to obtain NH4X pellets.
[0112] The NH4X pellets were sprayed with 0.05 mol / L barium nitrate solution while turning them over until the pellets were completely wetted (so that the solution came into contact with the pellets in the form of spray droplets), and then allowed to stand for 90 minutes. After drying, they were calcined at 400°C for 3 hours.
[0113] The barium exchange degree of the prepared BaX molecular sieve is 98.8%. The adsorption capacity and selectivity test results are shown in Table 1.
[0114] Example 6
[0115] The ratio of NaX molecular sieve and bentonite is 80:20;
[0116] The NaX molecular sieve and bentonite are mixed in a certain proportion, and then lignin accounting for 5wt% of the total dry weight of the molecular sieve and bentonite is added, and the mixture is fully stirred and rolled to form small balls with a particle size of 0.3-1mm.
[0117] The pellets were dried at 180°C and then calcined at 550°C for 8 hours to obtain an adsorbent precursor, which was crystallized in an alkaline solution.
[0118] The crystallized pellets were placed in a stainless steel tube container and 0.2 mol / L ammonium sulfate solution was introduced until the sodium content in the outlet solution was less than 0.1 wt%. The exchange temperature was 70°C and the volume space velocity was 4 h -1 . Wash and dry to obtain NH4X pellets.
[0119] The NH4X pellets were sprayed with 0.1 mol / L barium chloride solution while turning them over until the pellets were completely wetted (so that the solution came into contact with the pellets in the form of spray droplets), left to stand for 80 minutes, and then dried and calcined at 50°C for 4 hours.
[0120] The barium exchange degree of the prepared BaX molecular sieve is 98.5%. The adsorption capacity and selectivity test results are shown in Table 1.
[0121] Example 7
[0122] The ratio of NaX molecular sieve and pearlite is 84:16;
[0123] The NaX molecular sieve and pearlite are stirred evenly, and a proper amount of polyethylene glycol aqueous solution is added while rolling to form the mixture, wherein the amount of polyethylene glycol added is 1wt% of the total dry weight of the molecular sieve and pearlite; the amount of the polyethylene glycol aqueous solution is 20wt% of the total dry weight of the molecular sieve and pearlite; and the particle size of the small balls is 0.3-1mm.
[0124] The pellets were dried at 110° C. and then calcined at 950° C. for 1 hour to obtain an adsorbent precursor. The adsorbent precursor was crystallized in an alkali solution to obtain crystallized pellets.
[0125] The crystallized pellets were placed in a stainless steel tube container and 0.2 mol / L ammonium chloride solution was introduced until the sodium content in the outlet solution was less than 0.1 wt%. The exchange temperature was 75 °C and the volume space velocity was 7 h -1 . Wash and dry to obtain NH4X pellets.
[0126] The NH4X pellets were sprayed with 0.15 mol / L barium chloride solution while turning them over until the pellets were completely wetted (so that the solution came into contact with the pellets in the form of spray droplets), and then allowed to stand for 100 minutes. After drying, they were calcined at 500°C for 1 hour.
[0127] The barium exchange degree of the prepared BaX molecular sieve is 98.7%. The adsorption capacity and selectivity test results are shown in Table 1.
[0128] Example 8
[0129] The ratio of NaX molecular sieve to halloysite is 95:5;
[0130] The NaX molecular sieve and halloysite are uniformly stirred in a certain proportion, and a proper amount of sodium carbonate aqueous solution is added while rolling and forming, wherein the amount of sodium carbonate added accounts for 4wt% of the total dry weight of the molecular sieve and halloysite; the amount of the sodium carbonate aqueous solution is 15wt% of the total dry weight of the molecular sieve and halloysite; and the particle size of the small balls is 0.3-1mm.
[0131] The pellets were dried at 170° C. and then calcined at 900° C. for 1 hour to obtain an adsorbent precursor. The adsorbent precursor was crystallized in an alkali solution to obtain crystallized pellets.
[0132] The crystallized pellets were placed in a stainless steel tube container and 0.05 mol / L ammonium carbonate solution was introduced until the sodium content in the outlet solution was less than 0.1 wt%. The exchange temperature was 75 °C and the volume space velocity was 5 h -1 . Wash and dry to obtain NH4X pellets.
[0133] The NH4X pellets were sprayed with 0.1 mol / L barium chloride solution while turning them over until the pellets were completely wetted (so that the solution came into contact with the pellets in the form of spray droplets), left to stand for 90 minutes, and then dried and calcined at 450°C for 2 hours.
[0134] The barium exchange degree of the prepared BaX molecular sieve is 98.9%. The adsorption capacity and selectivity test results are shown in Table 1.
[0135] Comparative Example 1
[0136] The relevant parameters involved in the preparation process of the adsorbent in this comparative example are the same as those in Example 1, and the only difference is the preparation process. The specific steps are as follows:
[0137] Mix NaX molecular sieve and kaolin evenly, and add appropriate amount of polyethylene glycol aqueous solution to form small balls while rolling;
[0138] The pellets are dried and then calcined to obtain an adsorbent precursor; the adsorbent precursor is crystallized in an alkali solution to obtain crystallized pellets;
[0139] The crystallized beads were placed in a stainless steel tube container, and a 0.5 mol / L barium chloride solution was introduced until the sodium content in the outlet solution was less than 0.1 wt %. The p-xylene adsorbent was then washed and dried.
[0140] The barium exchange degree is 99.0%. The adsorption capacity and selectivity test results are shown in Table 1.
[0141] Depend on Figure 1 It can be seen that the BaX adsorbent prepared by the method of Example 1 and the conventional ion exchange method shown in this comparative example have the same molecular sieve framework structure and equivalent crystallinity, and no BaO diffraction peak appears, indicating that Ba 2+ Evenly distributed.
[0142] Comparative Example 2
[0143] The relevant parameters involved in the preparation process of the adsorbent in this comparative example are the same as those in Example 2, and the only difference is the preparation method. The specific steps are as follows:
[0144] The NaX molecular sieve and bentonite are mixed, and then starch is added, and the mixture is fully stirred and rolled to form small balls.
[0145] The pellets are dried and calcined to obtain an adsorbent precursor, and the adsorbent precursor is crystallized in an alkali solution to obtain crystallized pellets.
[0146] The crystallized balls (NaX balls at this time) are turned over and sprayed with barium chloride solution until the balls are completely wetted. The barium content in the solution is theoretically such that the barium exchange degree of the NaX balls reaches 99%.
[0147] The mixture is allowed to stand, dry and calcine to allow barium ions to replace sodium ions and enter the exchange sites of the molecular sieve, and then the exchanged sodium is washed away with deionized water.
[0148] The barium exchange degree of the adsorbent obtained after drying is 63.2%. The adsorption capacity and selectivity test results are shown in Table 1.
[0149] Comparative Example 3
[0150] The relevant parameters involved in the preparation process of the adsorbent in this comparative example are the same as those in Example 1, and the only difference is the preparation method. The specific steps are as follows:
[0151] The NaX molecular sieve powder is ammonium exchanged with an ammonium chloride solution, washed and dried to obtain the NH4X molecular sieve powder. The NH4X molecular sieve powder is sprayed with a 0.1 mol / L barium chloride solution while stirring until the sample is completely wetted. The barium content in the solution is such that the barium exchange degree of the NH4X molecular sieve reaches 99% in theory.
[0152] After the above sample is dried, it is evenly mixed with kaolin, and a proper amount of polyethylene glycol aqueous solution is added while rolling to form small balls, which are then dried and roasted.
[0153] The parameters such as ratio, temperature, time, etc. in the above process are the same as those in Example 1.
[0154] The adsorption capacity and selectivity test results are shown in Table 1.
[0155] Comparative Example 4
[0156] The relevant parameters involved in the preparation process of the adsorbent in this comparative example are the same as those in Example 1, and the only difference is the preparation method, which is as follows:
[0157] Mix NaX molecular sieve and kaolin evenly, and add appropriate amount of polyethylene glycol aqueous solution to form small balls while rolling;
[0158] The pellets are dried and then roasted to obtain an adsorbent precursor; the adsorbent precursor is crystallized in an alkaline solution to obtain crystallized pellets; and the crystallized pellets are ammonium exchanged to obtain NH4X pellets.
[0159] Place the NH4X pellets directly into the barium chloride solution and gently stir until the solution is completely absorbed by the pellets. The amount of the barium chloride solution is the saturated water absorption of the NH4X pellets. After standing, drying and calcining, the adsorbent is obtained.
[0160] Due to the uneven distribution of the barium solution, a batch of small balls were tested, and the barium exchange degree of the obtained adsorbent was 85.6-102.5wt%. The adsorption capacity and selectivity test results are shown in Table 1.
[0161] Comparative Example 5
[0162] The relevant parameters involved in the preparation process of the adsorbent in this comparative example are the same as those in Example 1, and the only difference is the preparation method, which is as follows:
[0163] Mix NaX molecular sieve and kaolin evenly, and add appropriate amount of polyethylene glycol aqueous solution to form small balls while rolling;
[0164] After drying the pellets, they are calcined to obtain an adsorbent precursor; the adsorbent precursor is crystallized in an alkali solution to obtain crystallized pellets; the crystallized pellets are ammonium exchanged to obtain NH4X pellets. The NH4X pellets are turned over and sprayed with barium chloride solution until the pellets are completely wetted (so that the solution contacts the pellets in the form of spray droplets), and then directly dried and calcined without standing to obtain an adsorbent.
[0165] The adsorption capacity and selectivity test results are shown in Table 1.
[0166] Comparative Example 6
[0167] The relevant parameters involved in the preparation process of the adsorbent in this comparative example are the same as those in Example 1, and the only difference is the preparation method, which is as follows:
[0168] Mix NaX molecular sieve and kaolin evenly, and add appropriate amount of polyethylene glycol aqueous solution to form small balls while rolling;
[0169] The pellets are dried and then roasted to obtain an adsorbent precursor; the adsorbent precursor is crystallized in an alkaline solution to obtain crystallized pellets; and the crystallized pellets are ammonium exchanged to obtain NH4X pellets.
[0170] The NH4X pellets were turned over and sprayed with barium chloride solution (so that the pellets were in contact with the barium chloride solution in the form of spray droplets), and then allowed to stand without filtering and directly dried and calcined to obtain an adsorbent. The barium content in the sprayed barium chloride solution was also such that the barium exchange degree of the NH4X molecular sieve reached 99% in theory, but the total volume of the barium chloride solution was twice that of Example 1, and the corresponding barium concentration in the barium chloride solution was reduced to one-half of that in Example 1 (i.e., 0.05 mol / L).
[0171] Due to the uneven distribution of the barium solution, a batch of small balls were tested, and the barium exchange degree of the obtained adsorbent was 77.6-108.3wt%. The adsorption capacity and selectivity test results are shown in Table 1.
[0172] Comparative Example 7
[0173] The relevant parameters involved in the preparation process of the adsorbent in this comparative example are the same as those in Example 1, and the only difference is the preparation method, which is as follows:
[0174] Mix NaX molecular sieve and kaolin evenly, and add appropriate amount of polyethylene glycol aqueous solution to form small balls while rolling;
[0175] The pellets are dried and then roasted to obtain an adsorbent precursor; the adsorbent precursor is crystallized in an alkaline solution to obtain crystallized pellets; and the crystallized pellets are ammonium exchanged to obtain NH4X pellets.
[0176] The NH4X pellets were turned over and sprayed with barium chloride solution (so that the NH4X pellets were in contact with the pellets in the form of spray droplets), then left to stand, and then dried and calcined to obtain an adsorbent. The barium content in the sprayed barium chloride solution was also such that the barium exchange degree of the NH4X molecular sieve reached 99% in theory, but the total volume of the barium chloride solution was reduced to one-half of that in Example 1, and the corresponding barium concentration in the barium chloride solution was increased to twice that in Example 1.
[0177] Due to the uneven distribution of the barium solution, a batch of small balls were tested, and the barium exchange degree of the obtained adsorbent was 64.8-109.5wt%. The adsorption capacity and selectivity test results are shown in Table 1.
[0178] Example 9
[0179] The relevant parameters involved in the preparation process of the adsorbent in this comparative example are the same as those in Example 1, and the only difference is the preparation method, which is as follows:
[0180] According to the method described in Example 1, the NH4X pellets are sprayed with the barium chloride solution while turning them over until the pellets are completely wetted (so that the barium chloride solution contacts the pellets in the form of spray droplets), and then allowed to stand and dry before being subjected to high temperature treatment;
[0181] The difference is that during the high temperature treatment, air with a certain humidity is continuously introduced, with the aim of making the volume content of water vapor in the gas atmosphere during the high temperature treatment be at a level of 20 to 40%.
[0182] The barium exchange degree of the prepared adsorbent is 99.1%. The adsorption capacity and selectivity test results are shown in Table 1.
[0183] Comparative Example 8
[0184] The relevant parameters involved in the preparation process of the adsorbent in this comparative example are the same as those in Example 1, and the only difference is the preparation method, which is as follows:
[0185] The NH4X pellets were sprayed with barium chloride solution while being turned over until the pellets were completely wetted (so that the barium chloride solution came into contact with the pellets in the form of spray droplets), and then allowed to stand and dry without being calcined.
[0186] The barium exchange degree of the prepared adsorbent is 98.6%. The adsorption capacity and selectivity test results are shown in Table 1.
[0187] Example 10
[0188] Adsorption capacity and selectivity test results. According to the above, the adsorbent was tested for adsorption capacity and selectivity, and the results are shown in Table 1.
[0189] Table 1 Adsorption capacity and adsorption selectivity of each sample
[0190]
[0191] Note: a refers to the molar amount of barium salt required to prepare 100g of adsorbent; b refers to the molar amount of barium salt in the waste liquid generated by preparing 100g of adsorbent.
[0192] It can be seen from Table 1 that:
[0193] In Examples 1 to 8, the p-xylene adsorbent prepared by the method of the present invention has similar adsorption performance to the conventional adsorbent prepared by liquid barium ion exchange (cation exchange) (Comparative Example 1), and does not generate barium-containing wastewater and has low production cost.
[0194] Comparative Example 2 directly loads barium without ammonium ion exchange. Since sodium ions are not as easily exchanged as ammonium ions, the barium exchange degree is low, resulting in poor selectivity of the adsorbent. Although the adsorption capacity of NaX molecular sieve is higher than that of BaX molecular sieve, NaX molecular sieve does not have adsorption selectivity, and the washing water contains not only the exchanged sodium ions but also the unexchanged barium ions, and barium-containing wastewater will still be generated.
[0195] Comparative Example 3: BaX molecular sieve powder is first prepared and then rolled with a binder to form the powder. Therefore, the binder cannot be crystallized, resulting in less effective active components of the adsorbent and lower adsorption capacity.
[0196] In Comparative Example 4, the barium solution is not sprayed but the pellets are directly placed in the barium solution, and the liquid is unevenly distributed, resulting in uneven distribution of barium.
[0197] Comparative Example 5 did not undergo a static treatment, and the barium solution did not fully diffuse into the pores of the molecular sieve, resulting in uneven distribution of barium, with a high barium content on the outer surface of the pellet and a low barium content inside.
[0198] In Comparative Example 6, the volume of the barium solution is excessive. During the drying process, due to the effect of gravity, the barium loading of the lower layer of balls is high while the barium loading of the upper layer of balls is low, and part of the barium does not enter the pores but is deposited on the surface of the balls.
[0199] In Comparative Example 7, the volume of the barium solution is insufficient, and the small balls in different parts absorb different amounts of the barium solution, resulting in uneven distribution of barium.
[0200] Comparative Examples 4 to 7 Due to the uneven distribution of barium, some acidic sites have no Ba 2+ protection, the molecular sieve structure partially collapsed during the calcination process, resulting in a lower adsorption capacity.
[0201] Example 9 After loading barium, the mixture was calcined at high temperature in a water vapor atmosphere. The water vapor promoted the formation of Ba 2+ Migration within the molecular sieve pores due to Ba 2+ The distribution is more uniform, resulting in higher adsorption capacity and adsorption selectivity.
[0202] In Comparative Example 8, after loading barium, no calcination treatment was performed, and the barium only entered the pores of the molecular sieve without being dispersed and reaching the exchange sites, so the adsorption activity was poor.
Claims
1. A method for preparing a molecular sieve type adsorbent, characterized in that: The molecular sieve type adsorbent is loaded with component M; The preparation of the molecular sieve type adsorbent comprises at least the following steps: S1. contacting, mixing, and forming the molecular sieve, the binder, and the pore-forming agent; S2. High temperature treatment to obtain product A; S3. subjecting product A to in-situ crystallization treatment in an alkaline system to obtain product B; S4. The product B is subjected to a target ion removal treatment to obtain a product C; wherein the target ions include ions derived from the alkaline system in S3; S5. The solution containing M is brought into contact with the product C in the form of small droplets, and then allowed to stand for treatment, and finally subjected to high temperature treatment in an atmosphere containing water vapor; Wherein, the time of the static treatment is 30 to 120 minutes; The volume content of water vapor in the gas atmosphere during the high temperature treatment is 20-40%, the temperature of the high temperature treatment is 350-500°C, and the time of the high temperature treatment is 1-5 hours; The saturated water absorption of the product C is determined, and the amount of the solution containing M does not exceed the saturated water absorption of the product C.
2. The method for preparing a molecular sieve type adsorbent according to claim 1, characterized in that: In S1, the amount of molecular sieve added is higher than the amount of binder added; The amount of the pore former added is 1-5wt% of the total dry weight of the molecular sieve and the binder.
3. The method for preparing a molecular sieve type adsorbent according to claim 1, characterized in that: In S2, the temperature of the high temperature treatment is 550-950°C; The high temperature treatment time is 1 to 8 hours.
4. The method for preparing a molecular sieve type adsorbent according to any one of claims 1 to 3, characterized in that: The component M is an alkaline earth metal cation.
5. The method for preparing the molecular sieve type adsorbent according to any one of claims 1 to 3, characterized in that: In S4, the solution containing ammonium ions is brought into contact with the product B, and the content of the target ions in the solution after the contact is detected. If the content of the target ions is ≤0.1 wt %, the removal treatment of the target ions is completed.
6. The method for preparing a molecular sieve type adsorbent according to any one of claims 1 to 3, characterized in that: The product B is placed in a container, and a solution containing ammonium ions is continuously introduced into the container; Wherein, the container has a liquid inlet and a liquid outlet; The temperature of the solution containing ammonium ions is 60-80°C, and the volume space velocity of the solution is 2-8 h -1 .
7. Use of the molecular sieve type adsorbent prepared by the method according to any one of claims 1 to 6, characterized in that: Used to obtain the target product from the mixture by adsorption separation; The target product includes p-xylene and / or p-cresol.
